IMPLEMENTASI KONSEP PENTA HELIX DALAM PENGURANGAN RESIKO BENCANA DI KOTA PROBOLINGGO - Devina Amelia Arifiyanti; Erwing Wahyu Millensyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Probolinggo City is an area that has a high level of vulnerability to various disaster threats, so disaster risk reduction is a regional development priority. The regional government has integrated disaster risk reduction policies through the RPJMD and RPB with the Penta Helix collaborative approach. This research aims to analyze the implementation of the Penta Helix concept in reducing disaster risk in Probolinggo City based on George C. Edwards III's policy implementation model. The research was conducted qualitatively through case studies using interview techniques, observation and document review. The research results show that the implementation of Penta Helix is ??quite effective, especially in the aspects of communication and bureaucratic structure with BPBD as coordinator. However, its implementation still faces limitations in the aspects of human resources, funding, and the role of the business world and academics in institutionalizing cross-sector collaboration is not yet optimal.